Stress-Coping Humoral Glycolipids Produced by Mice Given Controlled Bathing Treatments. (3rd November 2019) - Masuda, Yutaka; Narita, Hiroto; Hasegawa, Hiroaki
Abstract : Mammalians have recognition-behavioral stress-coping neuronal module system followed by some humoral glycolipids. A sulfated Galbeta1-4GlcNAc-lipid promotes the serotonergic module regulating the emotional behaviors for not-wasting the physical strength; GalNAcalpha1-3GalNAc-lipid promotes the adrenergic module inducing the behaviors escaping from the uneasy situation, and sulfated Fucalpha1-2Gal-lipid protects the cholinergic module keeping the stressor-memory from the ischemia-stress. Mouse given bathing recognizes the stressors to be coped with in the treatment. We previously observed mouse given CO2 -microbubble-bathing increased the behavior escaping from the bathing situation. Mouse given CO2 -microbubble-bathing would recognize the other stressors to be coped with in the treatment. We examined stress-coping glycolipids produced by mice given controlled bathing treatments, and got the following results. A sulfated Galbeta1-4GlcNAc-lipid production was increased by the acidic bathing condition and the dissolved CO2, GalNAcalpha1-3GalNAc-lipid production was increased by the dissolved CO2, and sulfated Fucalpha1-2Gal-lipid production was increased by the acidic bathing condition. We understood the mice treated with CO2 -microbubble-bathing would recognize the acidic bathing condition and the dissolved CO2, but not the microbubble, as the other stressors to be coped.